Creatures of Empire how domestic animals transformed early America - Anderson, Virginia DeJohn; Oxford eBooks (Oxford : Oxford University Press, 2004)
In keeping livestock, early American settlers inadvertently laid the groundwork for expansionism, as shown in a fascinating look at the earliest conflicts between the American colonists and the Native Americans, conflicts that had their roots in the domestication of animals.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Livestock -- United States -- History; Livestock -- Social aspects -- United States -- History; Human-animal relationships -- United States -- History; Indians, Treatment of; United States -- History -- Colonial period, ca. 1600-1775.; America -- Colonization -- Social aspects; Electronic books